Mechanical Mechanism of Fault Dislocation Based on in situ Stress State - Shi, Haoyu; Huang, Fuqiong; Ma, Zhenkai; Wang, Yongjian; Feng, Jicheng; Gao, Xu (Frontiers in Earth Science, 2020)
Fault dislocation occurs under certain stress conditions. Based on the mechanical relationship between the direction of crustal stress and the occurrence of fault plane, three criterions of fault strike dislocation trend, dip dislocation trend and fault dislocation or not are put forward, According to these three criteria, the fault slip and the type of slip can be inferred. The parameters that have great influence on the characteristics of fault slip are: fault dip angle, angle between horizontal principal stress and fault strike, depth, lateral pressure coefficient, internal friction angle and cohesion of fault plane. Fault slip is more likely to occur in the environment of high deviation stress, low friction angle and dip angle of about 40°. Fault rupture is a point-to-surface and deep-to-shallow process. When the criterion f2 of the local position of the fault is greater than 0, it will lead to the slip of the nearby fault. When the slip range of the fault extends to the surface, it will cause large earthquakes with large-scale surface rupture. The theoretical calculation is basically consistent with the numerical simulation results. According to the theory in this paper, the slip instability state of Longmen Mountain Fault Zone under different stress conditions is calculated, the results show that when the lateral pressure coefficient is greater than 2.5, dislocation occurs in the deep part of the fault.